2013
DOI: 10.1111/1462-2920.12318
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the marine bacterial genus Glaciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation

Abstract: To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of Glaciecola, a recently defined cold-adapted genus with species from diverse marine locations, to study the genomic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 60 publications
4
51
1
Order By: Relevance
“…An OTU related to Psychroflexus torques, which is known to associate with ice algae (Bowman et al, 1998) and may oxidize dimethylsulfoniopropionate, was also exclusive to the core MYI group. One of the OTUs was closely related to Glacicola nitratireducens (Supplementary Table S3), which is involved in the nitrogen cycle through denitrification (Qin et al, 2014). The fact that these Glacicola sequences are found in high abundance in all MYI samples may explain a previous observation that denitrification occurs much more strongly in MYI than in FYI (Rysgaard et al, 2008).…”
Section: Myi and Fyi Have Distinct Membership But Not Compositionmentioning
confidence: 83%
See 1 more Smart Citation
“…An OTU related to Psychroflexus torques, which is known to associate with ice algae (Bowman et al, 1998) and may oxidize dimethylsulfoniopropionate, was also exclusive to the core MYI group. One of the OTUs was closely related to Glacicola nitratireducens (Supplementary Table S3), which is involved in the nitrogen cycle through denitrification (Qin et al, 2014). The fact that these Glacicola sequences are found in high abundance in all MYI samples may explain a previous observation that denitrification occurs much more strongly in MYI than in FYI (Rysgaard et al, 2008).…”
Section: Myi and Fyi Have Distinct Membership But Not Compositionmentioning
confidence: 83%
“…Both of these genera are known to have a role in the degradation of dimethylsulfoniopropionate originating from marine algae (Gonzalez et al, 1999;Moran et al, 2007). Other OTUs were members of the genus Glacicola (Supplementary Table S3) known for their role in hydrolyzing complex organic carbon molecules such as cellulose and chitin originating from algae (Qin et al, 2014). An OTU related to Psychroflexus torques, which is known to associate with ice algae (Bowman et al, 1998) and may oxidize dimethylsulfoniopropionate, was also exclusive to the core MYI group.…”
Section: Myi and Fyi Have Distinct Membership But Not Compositionmentioning
confidence: 99%
“…As a reference, in the comparison of 7 species of the genus Pseudomonas which genome has a similar genome size to the genus Alteromonas , were found ca .1500 genes making up the core [63]. In the same way, 11 species of the genus Glaciecola that belong to the same family had 1257 genes [64]. Actually, from the ANI values A. macleodii could be in really composed of at least 3 species, the strains defined as the deep ecotype, the yellow sea isolate and the global surface ecotype with ANIs ranging from 73.7 to 80.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible part of the genome thus far would add up to ca . 13000 genes, also a typical value if is compared with the marine bacteria of the related genus Glaciecola (17276 gene families) [64] or the more than 17000 of the Vibrio pangenome [65]. …”
Section: Discussionmentioning
confidence: 99%
“…Adaptation by the genus Glaciecola to low temperatures and cold environments is suggested by a number of studies. A recent metagenomic analysis of the genus Glaciecola identified several cold-adapted mechanisms in the pan-genome that would allow the survival and growth of this genus at low temperatures (Qin et al, 2014). Although cold environments (e.g., in polar regions) seem to be the favored habitat of Glaciecola (Bowman et al, 1998; Nichols et al, 1999; van Trappen et al, 2004; Zhang et al, 2006; Prabagaran et al, 2007), its members have also been found in Mediterranean coastal waters (Alonso-Sáez et al, 2007) and during a phytoplankton spring bloom in the North Sea (Teeling et al, 2012).…”
Section: Discussionmentioning
confidence: 99%